(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The development of effective approaches aimed at improving the psycho-emotional state of war veterans is due to the need for their social adaptation, improvement of the general state of health after the stress experienced, physical and psychological injuries. A considerable number of studies indicate that physical activity, including fitness training, has a positive effect on a person’s physical condition. Effective means that can eliminate the negative consequences of emotional overstrain are SPA procedures. The search for ways of comprehensive use of SPA and fitness equipment is relevant. The purpose of the study is to substantiate and develop a comprehensive fitness program using SPA procedures aimed at normalizing the psycho-emotional state of male war veterans and to determine its effectiveness. The vast majority (78.6%) of male veterans have an average level of stress. The level of personal anxiety is moderate at 57.2%, and situational anxiety is 64.3%. The data obtained served as the basis for developing a program that involves the integrated use of fitness equipment (cardio, strength training and stretching) and SPA procedures. The program is designed for three months, includes 24 training sessions, each lasting 60 minutes. The program includes SPA procedures that have a beneficial effect on the normalization of a person’s psycho-emotional state: anti-stress massage, “Magic of Chocolate” wrap and coffee peeling, underwater shower-massage, alpha capsule, Charcot shower, general massage and Finnish bath (sauna). The effectiveness of the program is proven by the positive dynamics of well-being, activity and mood indicators of male war veterans, as well as indicators of the physical and mental components of their quality of life.